Novel prion mutation (p.Tyr225Cys) in a Korean patient with atypical Creutzfeldt–Jakob disease - Bagyinszky, Eva (Clin Interv Aging, 2019)
Background: A novel prion variant, PRNP p.Tyr225Cys (c.674A>G; p.Y225C), was identified in an atypical Creutzfeldt–Jakob disease (CJD) patient. The patient had a 5-year history of progressive cognitive impairment with speech and gait disturbances. From the basic neurological examination at his first hospital visit, rigidity and myoclonic jerks in all limbs were observed without focal weakness. Electroencephalogram showed the diffuse slow continuous delta activity in the bilateral cerebral hemisphere. Magnetic resonance imaging revealed abnormalities in the brain, such as cortical signal changes and edema in the frontotemporoparietal lobes and the basal ganglia. Cerebrospinal fluid 14–3-3 protein analysis showed a weakly positive signal. Family history remained unclear, but the patient’s mother and sister were diagnosed with cognitive impairment but both refused genetic testing. Methods: Targeted next generation sequencing (NGS) was performed on 50 genes, involved in different neurodegeneratives diseases, such as Alzheimer's, Parkinson's, frontotemporal dementia or prion diseases. In silico analyses and structure predictions were performed on the potential patohgenic mutations. Results: NGS and standard sequencing revealed the novel PRNP p.Tyr225Cys mutation in the patient. Structure predictions revealed that this may make the helix more flexible. In addition, the extra cysteine residue in TM-III of prion protein may result in disturbances of natural disulfide bond. Conclusion: Hence, the pathogenicity of PRNP p.Tyr225Cys was not fully confirmed at present, and its penetrance was suggested to be low. However, its possible pathogenic nature in prion diseases cannot be ignored, since Tyr/Cys exchange could disturb the helix dynamics and contribute to conformational alteration and disease progression.